A scientometric review on mechanical and durability performance of geopolymer Paste: Effect of various raw materials. (22nd August 2022) - Raza, Ali; Hechmi El Ouni, Mohamed; Azab, Marc; Ali, Khawar; Haider, Hammad; Rashedi, Ahmad
Highlights: An extensive review on geopolymer paste (GPL) for mechanical and durability behavior. Microstructural assessment of fly ash (FA) and FA-slag GPL paste. Assessment of different properties of GPL for various raw materials. Assessment of durability performance of GPL for various raw materials. Abstract: Geopolymer (GPL) paste has recently become a promising ecological substitute for conventional cementitious composites. They are environmentally friendly and cost-effective, and their manufacture involves a relatively small amount of energy. GPL is alkali-activated pastes made up of base materials that can be utilized for concrete structures, ensuring environmental sustainability and enabling cost-effective construction. This research assesses the microstructural aspects of fly ash (FA) and FA-slag GPL paste, fresh characteristics including workability and setting time, hardened characteristics including compressive strength (CS), and splitting tensile strength (STS), and durability characteristics. The influence of various forms of alkaline solution, the concentrations of alkaline solution, the integration of various kinds of alkaline activators, the alkaline solution to the binding material ratio (S/B), the ratio of fine aggregate to binding material, curing duration and temperature, and the influence of multiple kinds of superplasticizers are investigated. The current work also examines the influence of several additives in FA-GPL and FA-slag GPL pastes, including nano-materials, different kinds of fibers, bio-additives, epoxy, alumina, quartz powder, alccofine, and silica fume (SF). The influence of mix proportioning on the durability, hardened, and fresh features of FA-GPL and FA-slag GPL mix was comprehensively discussed in this work. The conclusions of the reviewed research papers are reported comprehensively.